ANTIOXIDANT ACTIVITY IN VITRO AND HEPATOPROTECTIVE EFFECT OF PHLOMIS MAXIMOWICZII IN VIVO - Gu, Haipeng; Gu, Xuezhu; Xu, Qitai; Kang, Wen-yi (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: A number of medicinal plants and there compounds played a major role in the treatment of hepatic disorders. They were widely used for the treatment of these disorders, and oxidant stress injury was one of the liver injury mechanisms. The present study evaluated the antioxidant activity and the hepatoprotective effect of each extracts of Phlomis maximowiczii. Materials and Methods: The antioxidant activity was assayed by the methods of ABTS, FRAP and DPPH in vitro. Hepatoprotective effect of P. maximowiczii extracts was examined using carbon tetrachloride-induced acute liver injury in mice. Results: P. maximowiczii n-butanol (PMBU) extract, ABTS (IC50=18.96 µg/mL), DPPH (IC50=25.15 µg/mL), and FRAP (RACT50=2775.6±144.18 µmol/g), showed higher scavenging capacity than that of P. maximowiczii ethyl acetate (PMEA). The n-butanol extract could significantly reduce the level of GPT, GOT and MDA (P<0.05, P<0.001 and P<0.001, respectively) and increase the level of SOD (P<0.001), respectively. Conclusion: The antioxidant activity of n-butanol extract in vitro was related with the level of MDA and SOD in vivo, and hepatoprotective effect of n-butanol extract also had relationship with its antioxidant activity in vivo.